Perilaku Hidup Bersih dan Sehat dengan Kejadian Penyakit Kulit - Patmawati Patmawati; Nurul Fitria Herman (Sarana Ilmu Indonesia (salnesia), 2021)
PHBS is a conscious health behavior to help yourself and your family in the health sectorand can participate in public health activities. The purpose of this study was to determine the relationship between clean and healthy living behavior with the incidence of skindiseases in the Sheikh Hasan Yamani Islamic Boarding School, Parappe Village, Camplagian District.This type of research is observational research, where the researcher conducts observations, interviews, and questionnaires as well as measures the variables studied, namely healthy behavior and skin diseases. This studi used cross sectional method. the HasanYamanistudents connected 585 students. The sample in this study was 88 students of Syekh Hasan Yamni Islamic Boarding School used random sampling, based on the results of the above data testing showed a significant value of p-value = 0,004 <? = 0,05. The results obtained are generally men who suffer from skin diseases because they do not maintain a cleanand healthy lifestyle when they are in the Hasan Yamani Islamic boarding school.